2017
DOI: 10.1088/1674-1056/26/11/114702
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic measurement of a large aircraft model in hypersonic flow

Abstract: Accurate aerodynamic measurements in the hypersonic flow of large aircraft models in tunnels have practical significance, but pose a significant challenge. Novel aerodynamic force measurement methods have been proposed,but lack theoretical support. The forms of the force signals techniques for signal processing and calculation of aerodynamics are especially problematic. A theoretical study is conducted to investigate the dynamic properties based on models of the draw-rod system and slender rods. The results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Unlike the conventional approach to change shape of a wing by mechanisms such as hinged flaps, some smart materials have been proposed and used in current airplane designs especially in unmanned aerial vehicle designs (UAV). [4] The ideal material for a morphing structure is an integration of load-carrying, deformability and low weight as discussed by Xavier et al [5] Until now, there have been several categories of materials concluded for morphing materials, and elastomer is a class of polymer having ability to undergo large strains with easy deforming talents because of its low stiffness. Anisotropic materials are also used for morphing designs for their stiffness are direction dependent which enable a structure to morph in a particular direction while stiff in others.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the conventional approach to change shape of a wing by mechanisms such as hinged flaps, some smart materials have been proposed and used in current airplane designs especially in unmanned aerial vehicle designs (UAV). [4] The ideal material for a morphing structure is an integration of load-carrying, deformability and low weight as discussed by Xavier et al [5] Until now, there have been several categories of materials concluded for morphing materials, and elastomer is a class of polymer having ability to undergo large strains with easy deforming talents because of its low stiffness. Anisotropic materials are also used for morphing designs for their stiffness are direction dependent which enable a structure to morph in a particular direction while stiff in others.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, aluminum alloy is a favorite choice for test models due to its relatively low density and excellent mechanical machining properties. It is a preferred model material for large impulse facilities, such as the JF12 shock tunnel, where the nozzle exit diameter amounts to 2.5 m. A typical test model has a length of 3-5 m and a weight of several hundred kilograms [16,17]. Aluminum significantly reduces the model weight; however, the significant difference in its thermal properties to those of the sensor leads to problems for the heat transfer measurements.…”
Section: Introductionmentioning
confidence: 99%